Body related Shame, Guilt, Dissatisfaction and Depression among University Students with Obesity - Aqsa Naveed, Umme Rubab Kazmi, Tusamma Haq, Maryam Bawer (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To explore the relationship among body related shame, guilt, dissatisfaction and depression among university students with obesity. Study design: Correlation research design was used. Place and duration: The sample was selected from four different public and private sector universities of Lahore, Pakistan and the research was conducted from February-June 2022. Methodology: Purposive sampling strategy was used to select sample (n=200). The Weight related Body Shame and Guilt Scale, Depression Scale from DASS-21 and Body Satisfaction Scale were administered on the participants along with demographic sheet. Results: Weight-related body shame has significant positive correlation with guilt (.72**), depression (.77**) and BMI (.72**). Furthermore, weight-related body shame (β=.34), weight-related body guilt (β=.28), general dissatisfaction (β= .81), head dissatisfaction (β=.30), and body dissatisfaction (β=.27) were found to be significant positive predictors of depression among university students with obesity. Female students with obesity had more body-related shame, general dissatisfaction, head and body dissatisfaction. Conclusion: This research is helpful to understand the role of body related shame and guilt in causing depression among students with obesity. Keywords: Obesity, body shame, guilt, dissatisfaction, depression